Incidence, Clinical Characteristics, Risk Factors, and Outcomes of Upper Gastrointestinal Bleeding in Patients With COVID-19: Results of the UMC-19-S12. Issue 1 (25th January 2022) - González González, Rebeca; Jacob, Javier; Miró, Òscar; Llorens, Pere; Jiménez, Sònia; González del Castillo, Juan; Burillo-Putze, Guillermo; Martín, Alfonso; Martín-Sánchez, Francisco J.; Lamberechts, Jorge G.; Alquézar-Arbé, Aitor; Higa-Sansone, Leopoldo; et al.
Abstract : Objective: The authors investigated the incidence, risk factors, clinical characteristics, and outcomes of upper gastrointestinal bleeding (UGB) in patients with coronavirus disease 2019 (COVID-19), who were attending the emergency department (ED), before hospitalization. Methods: We retrospectively reviewed all COVID-19 patients diagnosed with UGB in 62 Spanish EDs (20% of Spanish EDs, case group) during the first 2 months of the COVID-19 outbreak. We formed 2 control groups: COVID-19 patients without UGB (control group A) and non-COVID-19 patients with UGB (control group B). Fifty-three independent variables and 4 outcomes were compared between cases and controls. Results: We identified 83 UGB in 74, 814 patients with COVID-19 who were attending EDs (1.11%, 95% CI=0.88-1.38). This incidence was lower compared with non-COVID-19 patients [2474/1, 388, 879, 1.78%, 95% confidence interval (CI)=1.71-1.85; odds ratio (OR)=0.62; 95% CI=0.50-0.77]. Clinical characteristics associated with a higher risk of COVID-19 patients presenting with UGB were abdominal pain, vomiting, hematemesis, dyspnea, expectoration, melena, fever, cough, chest pain, and dysgeusia. Compared with non-COVID-19 patients with UGB, COVID-19 patients with UGB more frequently had fever, cough, expectoration, dyspnea, abdominal pain, diarrhea, interstitial lung infiltrates, and ground-glass lung opacities. They underwent fewer endoscopies in the ED (although diagnoses did not differ between cases and control group B) and less endoscopic treatment. After adjustment for age and sex, cases showed a higher in-hospital all-cause mortality than control group B (OR=2.05, 95% CI=1.09-3.86) but not control group A (OR=1.14, 95% CI=0.59-2.19) patients. Conclusions: The incidence of UGB in COVID-19 patients attending EDs was lower compared with non-COVID-19 patients. Digestive symptoms predominated over respiratory symptoms, and COVID-19 patients with UGB underwent fewer gastroscopies and endoscopic treatments than the general population with UGB. In-hospital mortality in COVID-19 patients with UGB was increased compared with non-COVID patients with UGB, but not compared with the remaining COVID-19 patients.